EVALUATION OF IMMUNOLOGICAL SHIFTS IN ADULTS AFTER IMMUNIZATION AGAINST INFLUENZA WITH A SUBUNIT-BASED, ABSORBED MONOVALENT VACCINE STRAIN A/CALIFORNIA/7/2009/(H1N1) - M. P. Kostinov; O. A. Terkacheva; S. N. Girova; N. E. Jastrebova; A. P. Cherdantsev (Медицинская иммунология)
Abstract.    Seventy    healthy    volunteers  were    immunized    with    influenza    subunit    vaccine    strain    A/California/7/2009  /  (H1N1),  in  order  to  test  possible  changes  in  auto-reactivity.  It  was  shown  that  the  vaccine  is  safe  and  immunogenic.  In  addition,  it  was  revealed  that  a  double  injection  of  the  vaccine  was  not  accompanied  by  development  of  autoantibody  response,  both  to  tissue  antigens    (specifically,    to    lung    tissue,    or    basic    myelin  protein),    and    to    those    against    non-tissue    antigens  (native  or  denatured  DNA).  In  some  cases,  application  of    the    vaccine    was    accompanied    by    a    significant  reduction  in  levels  of  autoantibodies.  It  was  also  noted  that  injection  of  the  vaccine  is  accompanied  by  a  reduction  in  total  IgE  levels  in  patients  with  increased  baseline  IgE  levels.  Following  double  injection  of  the  vaccine  at  a  single  dose  of  0.5  ml,  the  frequencies  of  seroconversion  was  71.4%,  seroprotection  levels  were  achieved  in  59,2%,  whereas  seroconversion  factor  proved  to  be  4.92,  thus  meeting  the  CPMP  criteria.  (Med.  Immunol.,  2011,  vol.  13,  N  1,  pp  35-40)